Academic competition for prototype development - Walker, Rubens Aguiar; Gutierrez, Ruben Huamanchumo; Santos, Marcos dos; Pereira, Natálya Regina Guimarães; Reis, Marcone Freitas dos (Brazilian Journal of Operations & Production Management, 2018)
The purpose of this article is to describe a development method in academic to designing products by industry management in a competitive and collaborative manner. The focus is to create toys for donation in a competitive project so the students get more involved with the purpose to learn. The developed method was a competition using recycled materials in a sustainable way. The final toys donation creates a delivery to the society, generating added value for the students. The findings are dynamic due to the increase of each semester, obtaining a better academic yield by the combination of theory and practice. The contribution is defined in the delivery of skills to the industry of competitive students for the job market, generating innovation without an expensive research process.